Activated platelets and platelet-leukocyte aggregates in the equine systemic inflammatory response syndrome. (May 2022) - Theuerkauf, Kim; Obach-Schröck, Carmen; Staszyk, Carsten; Moritz, Andreas; Roscher, Katja A.
In humans, activated platelets contribute to sepsis complications and to multiple organ failure. In our prospective analytical study of cases of the equine systemic inflammatory response syndrome (SIRS), we adapted a standard human protocol for the measurement of activated platelets and platelet-leukocyte aggregates (PLAs) in equine platelet-leukocyte-rich plasma (PLRP) by flow cytometry, and we investigated the hypothesis that activated platelets and PLAs are increased in clinical cases of SIRS. We included 17 adult horses and ponies fulfilling at least 2 SIRS criteria, and 10 healthy equids as controls. Activation of platelets was determined by increased expression of CD62P on platelets. Activated platelets and PLAs were measured before and after in vitro activation of platelets with collagen. Median expression of CD62P on platelets was significantly increased after activation in the control group: 1.45% (interquartile range [IQR]: 1.08–1.99%) initially versus 8.78% (IQR: 6.79–14.78%, p  = 0.002) after activation. The equids with SIRS had significantly more activated platelets and PLAs in native PLRP than controls: CD62P 4.92% (median, IQR: 2.21–12.41%) versus 1.45% in controls (median, IQR: 1.08–1.99%, p  = 0.0007), and PLAs 4.16% (median, IQR: 2.50–8.58%) versus 2.95% in controls (median, IQR: 1.57–3.22%, p  = 0.048). To our knowledge, increased platelet activation and PLAs have not been demonstrated previously with flow cytometry in clinical cases of equine SIRS.